Efforts to Improve Students' Knowledge of Fundamental Movements Using the "Stop" Method in Physical Education Lessons for Grade V at SDN Sembilangan - Dwi Khusnul Khotimah; Rosida Afkarina; Nuri Junanul Firdausiyah; Weny Adelia Febri; Aida Nihayatul Labibah (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2026)
This study aims to improve students' basic movement knowledge through the application of the STOP (Stop, Think, Observe, Practice) method in Physical Education, Sports, and Health (PJOK) learning in grade V of Sembilangan Elementary School. The background of this study is the low understanding of students towards the concepts and techniques of basic movements, where students tend to only imitate movements without understanding the correct steps and objectives. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, action implementation, observation, and reflection. The subjects of the study were 30 grade V students of Sembilangan Elementary School. Data collection techniques used observation, interviews, and documentation. Data were analyzed quantitatively and qualitatively. The results of the study indicate that the application of the STOP method can improve students' basic movement knowledge. This is indicated by an increase in the average value and percentage of student learning completion from cycle I to cycle II. In addition, student activity in learning also increased, where students became more active, focused, and understood the concept of movement better. Thus, it can be concluded that the STOP method is effective for improving students' basic movement knowledge in PJOK learning in elementary schools.